Avaliação do uso do ozônio na sanitização de facas e na eliminação de Salmonella sp. em língua suína - Monteiro, Jeniffer Caroline (2021)
The food industry increasingly needs resources to increase products processing technology in order to meet the demands of consumers who demand increasingly stringent hygiene and food safety standards in addition to extending the shelf life of food. In a slaughterhouse, product contamination can occur in several stages, ranging from the procedures that precede the slaughter and after slaughter. Thus, the hygiene procedure becomes indispensable to guarantee the sanitary quality of the food. In the quest to minimize the effects of chemicals, research has been carried out with the use of ozone for the purpose of sanitization / disinfection, which stands out for its high oxidation potential and does not generate waste. The objective of the research was to evaluate the effectiveness in the elimination of pathogens through the use of ozonized water in the sanitization of knives used in the swine slaughter line and in the water for cooling the porcine tongue. The microbiological analyzes carried out to monitor the contamination of the knives were the counting of Aerobic Mesophiles and Escherichia coli and, to assess the quality of the tongue, the search for Salmonella sp. In the treatment of knives with ozonized water, there was a reduction in the count of aerobic mesophiles in 90% of the samples and for the porcine tongue, 27,2% of the samples with the presence of Salmonella sp. had the elimination of the pathogen after treatment. However, the low efficiency in eliminating Salmonella sp. it may be related to the control of ozone concentration, temperature and the presence of organic matter in water, indicating the need for further studies.